An appraisal of experimental designs: Application to enantioselective capillary electromigration techniques - Perovani, Icaro Salgado; Serpellone, Carolina Oliveira; de Oliveira, Anderson Rodrigo Moraes [UNESP] (Wiley, 2021)
Enantioresolution processes are vital tools for investigating the enantioselectivities of chiral compounds. An analyst resolves to optimize enantioresolution conditions once they are determined. Generally, optimization is conducted by a one-factor-at-a-time (OFAT) approach. Although this approach may determine an adequate condition for the method, it does not often allow the estimation of the real optimum condition. Experimental designs are conducive for the optimization of enantioresolution methods via capillary electromigration techniques (CETs). They can efficiently extract information from the behavior of a method and enable the estimation of the real optimum condition. Furthermore, the application of the analytical quality by design (AQbD) approach to the development of CET-based enantioselective methods is a trend. This article (i) offers an overview of the application of experimental designs to the development of enantioselective methods from 2015 to mid-2020, (ii) reveals the experimental designs that are presently employed in CET-based enantioresolutions, and (iii) offers a critical point of view on how the different experimental designs can aid the optimization of enantioresolution processes by considering the method parameters.
Keywords: Capillary electromigration techniques; Design of experiments; Enantioresolution; Experimental design; Optimization